La adolescencia y su identidad cultural - Narvaez Zavaleta, Jansen Santiago (2019)
The present work of professional proficiency entitled "Adolescence and its cultural identity", aims to explain and support, by means of a learning session to the students of the fourth year of the IE RAFAEL NARVAEZ CADENILLAS._x000D_ That the adolescents nowadays have lost the great importance of identifying with their culture, their traditions, their clothing, their ethnic diversity; facing with this, there is a need to let students know how to build our identity and how to develop a sense of belonging._x000D_ With this purpose, a great diversity of learning strategies has been used, such as motivation, previous knowledge, cognitive conflict among others. That they manage to awaken interest in students in order to be used by them._x000D_ The present work consists of three parts: in the first one, the methodological strategies of the application of the learning session have been elaborated; in the second, the scientific support with the help of supporting quotes is presented; and in the third, the psych pedagogical sustenance.